Estimasi kedalaman batuan dasar menggunakan metoda geolistrik tahanan jenis konfigurasi dipole-dipole di Universitas Negeri Padang Kampus Air Tawar (The estimation of bedrock depth using the geoelectric resistivity method of dipole-dipole configuration at the Universitas Negeri Padang Air Tawar) - Media Febrina; - Akmam; Fatni Mufit (PILLAR OF PHYSICS, 2013)
Estimation of basement rocks depth has been done in Padang State University, Air Tawar campus. The research that uses Dipole-dipole resistivity geoelectrical method was aimed to determine the depth, resistivity value and the kinds of basement rocks. Data were collected by Ares Multielectrode in 4 lines. Processing of data was done using Res2dinv software with Robust Constraint inversion and it results 2D model of earth’s surface that consists of depth and resistivity value. The result of this research shows that there are basement rocks around sounding point 00053’44,0”S and 100020’79,8”E in 1st line and sounding point 00053’53,1”S and 100021’02,8”E in 2nd line at depth of more than 25,2 m with resistivity value 513 – 622 Ωm and 632 – 2150 Ωm. Basement rocks are also found in 3rd line around sounding point 00053’48,9”S dan 100020’50,6”E at depth of more than 21,85 m with resistivity value 596,5 – 734 Ωm, while 4th line at sounding point 00053’55,7”S and 100021’02,3”E did not find basement rocks. Possibility of basement rocks in 4th line are at depth of more than 29,5 m. Basement rocks that are found in this research is interpreted as Andesite. Information about basement rocks can be used for construction planning in Padang State University, Air Tawar campus. Keywords: basement rocks, resistivity geoelectrical method, Dipole-dipole, Padang State University